The effect of combining HIIT and dry-land training on strength, technique, and 100-m butterfly swimming performance in age-group swimmers: a randomized controlled trial - Sofiene Amara; Raouf Hammami; Rodrigo Zacca; Jorge Mota; Yassine Negra; Sabri Gaied Chortane (Biology of Sport, 2022)
Combined interventions of pool-based and dry-land workouts are a common practice in swimming training. However, the effects on strength, technique and swimming performance are still not clear. Through a randomized controlled trial study, we investigated the effect of combining high intensity interval training (HIIT) and maximum strength training (MST) on strength, technique and 100-m butterfly swimming performance. Competitive age-group swimmers (N = 22, males) were randomly divided into two groups. The experimental group (EG: 14.1 ± 0.3 years old) performed 8 weeks of combined short-moderate HIIT and MST. The control group (CG: 14.5 ± 0.3 years old) subjects performed their usual training. Muscular strength, technique and swimming performance were evaluated before and after 8 weeks. Substantial improvements were observed in maximum muscle strength (mean diff: 22–28%; p  <  0.001; d =  3.25–3.61), technique (p  <  0.05; d = 0.98–1.96) and 100-m butterfly swimming performance (3.5%; p = 0.001; d = 1.81) when combining HIIT and MST during 8 weeks. Combining short-moderate HIIT and MST during 8 weeks can enhance maximum muscular strength, technique, and 100-m butterfly swimming performance. Coaches should adjust training programmes accordingly since it could yield important differences in swimming performance during competitions.